Whistleblowing as a Protracted Process: A Study of UK Whistleblower Journeys - Vandekerckhove, Wim (Journal of business ethics, 2019)
This paper provides an exploration of whistleblowing as a protracted process, using secondary data from 868 cases from a whistleblower advice line in the UK. Previous research on whistleblowing has mainly studied this phenomenon as a one-off decision by someone perceiving wrongdoing within an organisation to raise a concern or to remain silent. Earlier suggestions that whistleblowing is a process and that people find themselves inadvertently turned into whistleblowers by management responses, have not been followed up by a systematic study tracking the path of how a concern is repeatedly raised by whistleblowers. This paper provides a quantitative exploration of whistleblowing as a protracted process, rather than a one-off decision. Our research finds that the whistleblowing process generally entails two or even three internal attempts to raise a concern before an external attempt is made, if it is made at all. We also find that it is necessary to distinguish further between different internal (e.g. line manager, higher management, specialist channels) as well as external whistleblowing recipients (e.g. regulators, professional bodies, journalists). Our findings suggest that whistleblowing is a protracted process and that this process is internally more protracted than previously documented. The overall pattern is that whistleblowers tend to search for a more independent recipient at each successive attempt to raise their concern. Formal whistleblower power seems to determine which of the available recipients are perceived as viable and also what the initial responses are in terms of retaliation and effectiveness.